Effect of type of granular activated carbon on DOC biodegradation in biological activated carbon filters - BAKIRCI, KOZET (ELSEVIER SCI LTD, 2010)
The purpose of this paper is to clarify the effect of the two different GAC types (steam activated or chemically activated) on DOC biodegradation in biological activated carbon (BAC) columns. For this purpose, raw water taken from a surface reservoir was fed to continuous-flow lab-scale biofiltration columns which were run for more than 18,000 bed volumes. The effect of pre-ozonation on DOC removal was also evaluated. Experimental results showed that biological activity inside the BAC columns extended the service life and the choice of filter material was crucial in BAC systems. The DOC biodegradation was higher in thermally activated carbon columns compared to the chemically activated one. The ability of GAC to better adsorb and retain organic compounds increased the chance of biodegradation. Contrary to expectations, pre-ozonation did not significantly enhance DOC biodegradation. Despite the high increase in biodegradable dissolved organic carbon (BDOC) upon ozonation, overall DOC biodegradation efficiencies did not differ from raw water. Overall, the DOC biodegradation in columns was higher than in most of the studies. This observation was primarily attributed to the low specific ultraviolet absorption (SUVA) values in raw water indicating a high biodegradability. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biological activated carbon; Ozonation; Chemically activated GAC; Steam activated GAC; Specific UV absorption; Biodegradation; NATURAL ORGANIC-MATTER; BIOFILTRATION PERFORMANCE; HUMIC SUBSTANCES; REMOVAL; ADSORPTION; TEMPERATURE; FILTRATION; OZONATION; IMPACT; OZONE